2001
DOI: 10.1046/j.1523-1755.2001.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant renal artery stenosis: The hemodynamic response to revascularization

Abstract: Percutaneous transluminal angioplasty and stenting are safe and effective procedures to normalize the functional changes sustained by hemodynamically significant artery stenosis after renal transplantation. Doppler ultrasound scanning is a reliable and reproducible technique to monitor the renal functional response to vascular reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
4
19
0
3
Order By: Relevance
“…We believe that these factors are even more important for the pediatric population, and strongly support PTA as the first-line treatment when an experienced team is available Expandable metallic prostheses have been used for stenosis of coronary, peripheral and renal arteries. Palmaz et al [15] first reported their use in native kidneys and since 1995 several papers reporting their use in RAS have been published [15,16,17,18,19,20]. We have placed a metallic stent in two of our patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We believe that these factors are even more important for the pediatric population, and strongly support PTA as the first-line treatment when an experienced team is available Expandable metallic prostheses have been used for stenosis of coronary, peripheral and renal arteries. Palmaz et al [15] first reported their use in native kidneys and since 1995 several papers reporting their use in RAS have been published [15,16,17,18,19,20]. We have placed a metallic stent in two of our patients.…”
Section: Discussionmentioning
confidence: 87%
“…The use of expandable metallic prostheses (stents) was reported for coronary, peripheral, and native renal vascular stenosis [15]. Its use in transplant RAS is limited and most papers include only adult patients [16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Gray-scale and intrarenal Doppler evaluations are then performed. Renal artery and vein examination are performed with Doppler mode in the final stage of transplant kidney examination (Platt, 1992;Rawashdeh et al, 2001;Ruggenenti et al, 2001;Tublin et al, 2003;Zubarev, 2001). …”
Section: Wwwintechopencommentioning
confidence: 99%
“…This may be because of intraparenchymal changes resulting from activation of cytokines with profibrotic activity, as has been proposed by Farmer et al in their report on native kidneys with atherosclerotic vascular disease (24). Similarly Ruggenenti et al did not find a significant improvement in the glomerular filtration rate after angioplasty for TRAS despite improvement of hemodynamic parameters (25). CONCLUSION Prox-TRAS is a rare but treatable disease that influences blood pressure and kidney function.…”
Section: Treatment and Outcome In Group Bmentioning
confidence: 87%